The Critical Role of the Research Community in Space Weather Planning and Execution. Issue 3 (6th March 2018) - Robinson, Robert M.; Behnke, Richard A.; Moretto, Therese
Abstract: The explosion of interest in space weather in the last 25 years has been due to a confluence of efforts all over the globe, motivated by the recognition that events on the Sun and the consequent conditions in interplanetary space and Earth's magnetosphere, ionosphere, and thermosphere can have serious impacts on vital technological systems. The fundamental research conducted at universities, government laboratories, and in the private sector has led to tremendous improvements in the ability to forecast space weather events and predict their impacts on human technology and health. The mobilization of the research community that made this progress possible was the result of a series of actions taken by the National Science Foundation (NSF) to build a national program aimed at space weather. The path forward for space weather is to build on those successes through continued involvement of the research community and support for programs aimed at strengthening basic research and education in academia, the private sector, and government laboratories. Investments in space weather are most effective when applied at the intersection of research and applications. Thus, to achieve the goals set forth originally by the National Space Weather Program, the research community must be fully engaged in the planning, implementation, and execution of space weather activities, currently being coordinated by the Space Weather Operations, Research, and Mitigation Subcommittee under the National Science and Technology Council. Key Points: The scientific research community has made important contributions to space weather that should be continued and encouraged Progress in space weather has been achieved largely through involvement of the research community in space weather planning/implementation The research community must continue to be supported and engaged in space weather going forward